AN IMPLEMENTATION OF LEAN CONCEPT WITH 5S TO ELIMINATE MATERIAL WASTE IN PRECAST FACTORY - Roland Gasenda Suryaningrat; Indradi Wijatmiko; Yatnanta Padma Devia (Rekayasa Sipil, 2023)
Precast industry is currently experiencing an increase in demand from consumers. Due to increasing demand, a wide variety of products, and push production systems, factories suffer from excess waste, disorganized workplaces, and unhealthy working environments, so it needs a method to overcome these problems. In overcoming this problem, research was carried out by implementing a lean concept with the concept of Seiri, Seiton, Seiso, Seiketsu, Shitsuke (5S) on the handling of waste materials that occur in the precast concrete production process. Material waste is obtained from interviews and analysis of the production cost budget assisted by the Pareto 80/20 method to determine materials that are included in the waste category. From the results of the Pareto analysis, it was found that 5 materials were wasted, namely Reinforcement Ã˜ 13, Concrete Sand, Wire, Oil Formwork Console, and PC Strand 12.7. Then the results are re-analyzed with cause analysis based on the results of brainstorming with a quantity surveyor, two material wastages were obtained, namely wire and formwork console oil. The waste will be repaired with the seiri concept in the form of making a warehouse near the work area, so that later it will eliminate material wastage so that it can save oil. 2930-liter console formwork and 5915 kilograms of wire, with a total cost savings of IDR 123,758.060